Paradigma Problema Keilmuan Islam dan Dampaknya terhadap Model Lembaga Pendidikan Islam di Era Kontemporer - Ahmad Ali Riyadi (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
This paper discusses the discourse of seeking non-dichotomic integral Islamic scholarship that developed among Muslim intellectuals and its impact on the model of Islamic education institutions, especially in Indonesia. In this case a new scientific paradigm that is integrated is not only required to combine the revelations of God and the findings of human thought, read integralistic holistic sciences, it will not result in understating the role of God or isolating humans so that they are alienated from the surrounding community and environment. This scientific knowledge gap has enough impact on the dynamics of knowledge and its implications in socio-religious life in Indonesian and world society.